John Fowles: Reflection on Method in Context of Radical Postmodernism (based on Essays Collections “Aristos,” “Wormholes,” Diaries and Interviews) - E. S. Amineva (Научный диалог, 2018)
John Fowles’s artistic method is considered in the context of radical postmodernism on the material of collections of essays, diaries and interviews of the writer. Attention is paid to the category of the author in the works of Fowles as one of the most famous English writers of the 20th century. The principles of the text construction and Fowles’s attitude to the classical tradition, modern literature and art are characterized. In particular, it is shown that the writer does not accept many provisions of postmodernism. It is noted that the category of the author occupies a large place in the creative conception of the writer. Against the background of many contemporary writers Fowles rejects the idea of the “death of the author,” but rather in all his work he tries to establish the author’s responsibility to the reader, speaks of the principle of “responsible game.” It is noted that Fowles as a writer of the 20th century by this is close to the classical Victorian tradition. The author raises a question about the axiological component of the Fowles’s writer conception, by what he is also close to the Victorian tradition. Special attention is paid to Fowles’ reflections on contemporary art and literature. Referring to the reflections of the writer of the 20th century on this issue, the author comes to conclusion that the classical tradition is much closer to Fowles than postmodernism, which does not recognize any values and priorities.